Method for oxidative depolymerization of waste blended textiles into alpha-hydroxy acid and terephthalic acid
By oxidation and depolymerization of catalysts under oxygen conditions, waste blended textiles are converted into α-hydroxy acids and terephthalic acids, solving the problem of difficult to efficiently depolymerize multi-component textiles in the prior art, and achieving efficient and green chemical recycling.
Patent Information
- Application Number
- CN202411668509.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to efficiently depolymerize multi-component waste blended textiles in one pot process, and multiple separation steps are required during the processing process, and the yield is not high.
The catalyst is used to perform oxidative depolymerization under air and/or oxygen conditions, and the waste blended textiles are converted into α-hydroxy acids and terephthalic acids to achieve an autocatalytic depolymerization process.
It realizes efficient depolymerization and conversion of waste blended textiles, with simple product composition and easy recycling, meeting green chemistry requirements, few process steps and high economic benefits.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycling waste blended textiles, and specifically discloses a method for oxidatively depolymerizing waste blended textiles into alpha-hydroxy acid and terephthalic acid. Background Art
[0002] The amount of waste blended textiles generated worldwide each year is in the tens of millions of tons. Waste blended textiles are extremely useful carbon resources, and their recycling and reuse is an important direction for the development of the next generation of green technology. Efficient catalytic conversion of these recycled wastes can not only promote green carbon cycle carbon reduction, but also be of great benefit to environmental protection. At present, a variety of catalytic conversion technologies have been developed for the recycling of waste blended textiles. For example, polyester can be depolymerized into corresponding monomers or upgraded and recycled into high-value chemicals. However, previous studies have often focused on single-component raw materials, while waste textiles in real life are often mixed products of multiple components. There are also some studies on the recycling of polyester-cotton mixtures, but each component is often treated separately. If you want to complete the recycling of each component in one pot, you still face some challenges.
[0003] In the prior art, in the conversion process of each component of the polyester-cotton mixture, either one of the components is separated and converted first, and then the remaining residual components are converted. For example, the article Sci. Adv., 2024, 10, eado6827; Chem. Eng. J. 2023, 470, 144032 and patent CN 202754932 U disclose the use of a catalyst to depolymerize the polyester in the blend into BHET or TPA monomers, completely retaining the structure of cotton, and the alcoholyzed polyester and cotton fibers are filtered through a polyester-cotton filter to achieve the separation of cotton fibers and polyester alcoholyzates; or the polyester and cotton are subjected to different reactions in a "one-pot" system. For example, the one-pot method hydrolyzes the polyester in the blend into monomers and converts cotton into HMF (Nature Communications, 2024, 15, 4498), but the yield is not high. In addition, this treatment method adds separation processes at the front end and the back end, respectively, and the yield of many reactions is not ideal due to the presence of other substances. Therefore, designing new catalytic reactions can, on the one hand, reduce the types of products from the product end and normalize the target products, thereby simplifying the separation and processing at the back end; on the other hand, from the perspective of reaction route process design, the interaction between different components of the mixture can be used to promote the depolymerization and conversion. Research on the catalytic conversion of mixed raw materials is both a challenge and an opportunity due to the greatly increased complexity of the reaction system. Summary of the invention
[0004] In order to solve the problems in the background technology, the present invention discloses a method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid. Under air and / or oxygen conditions, a catalyst is used in a "one-pot method" to depolymerize the polyester-cotton mixture into PTA and α-hydroxy acid, providing a green, efficient and environmentally friendly chemical recycling method for mixed textile waste, thereby promoting the sustainable development of the textile industry.
[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0006] The method for oxidative depolymerization of waste blended textiles into α-hydroxy acids and terephthalic acid specifically comprises the following steps: adding waste blended textiles, a solid acid catalyst, and a reaction solution into a catalytic reactor, filling a certain amount of air and / or oxygen, heating to a specified temperature and stirring to carry out oxidative depolymerization, and after the reaction is completed, filtering, concentrating, separating and purifying the products to obtain terephthalic acid and α-hydroxy acids, wherein the α-hydroxy acids include glycolic acid and lactic acid.
[0007] Furthermore, the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, wherein the main components of the blended textiles are cotton and / or polyester.
[0008] Furthermore, the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, wherein the blended textiles also include one or a mixture of nylon, acrylic fiber, vinylon, acetate fiber, lyocell, polyester, and polyurethane.
[0009] Furthermore, in the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, the solid acid catalyst comprises at least one metal and its oxide and at least one carrier.
[0010] Furthermore, in the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, the metal in the solid acid catalyst is a mixture of one or more of Pt, Ru, Ir, Mo, Cu, Co, Ni, Sn, Fe, W, Cr, Nb, and La.
[0011] Furthermore, in the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, the carrier is a mixture of one or more of Al2O3, TiO2, ZrO2, SiO2, CeO2, ZSM-5 molecular sieve, Beta molecular sieve, Y-type molecular sieve, and activated carbon.
[0012] Furthermore, the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, and the solid acid catalyst, the synthesis method of which includes impregnation method, hydrothermal method, deposition precipitation method, and sol-gel method.
[0013] Furthermore, in the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, the mass ratio of the catalyst to the waste blended textiles is 1:1 to 1:20, preferably 1:2 to 1:10.
[0014] Furthermore, in the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, the mass proportion of the waste blended textiles in the solvent is 0.1 to 100%, preferably 1 to 50%.
[0015] Furthermore, in the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, the reaction solution is a mixture of one or more of water, methanol, ethanol, isopropanol, acetonitrile, acetone, tetrahydrofuran, dichloromethane, alkanes, and cycloalkanes.
[0016] Furthermore, in the method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, the reaction temperature is 180 to 250° C. and the reaction time is 10 to 40 hours.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The invention discloses a method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid. The terephthalic acid and α-hydroxy acid are both depolymerization products of the blended textiles and can also be used as catalysts to participate in the depolymerization of the blended textiles, thereby realizing an autocatalytic process of depolymerization and transformation of the waste blended textiles. The waste blended textiles are selectively oxidatively depolymerized into α-hydroxy acid and terephthalic acid. The product composition is simple and easy to recycle. The carbon atoms in the raw materials are fully utilized, which meets the requirements of green chemistry. The "one-pot method" for depolymerization and transformation of multiple components in the waste blended textiles is realized, and the process steps are few, the economic benefits are high, and the actual operation is simple.
[0019] The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid disclosed in the present invention is not only applicable to the recycling of blended textiles with cotton and polyester as main components, but also applicable to the depolymerization and recycling of a mixture of blended textiles and polyester waste plastics and waste paper. DETAILED DESCRIPTION
[0020] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0021] (1) Preparation of catalyst
[0022] Preparation of Ni-W / Al2O3: Nickel nitrate, tungsten chloride, Al2O3 and urea were dissolved in deionized water, mixed well and put into a hydrothermal kettle, and reacted in an oven at 100℃ for 24h. The product was collected by centrifugation, washed with water and ethanol until neutral, and then dried in an oven. The resulting white powder was calcined in air at 550℃ for 3h, and then reduced in hydrogen at 450℃ for 5h. Finally, it was aged in a mixed gas of N2:air at a ratio of 5:1 for 0.5h.
[0023] The preparation method of Nb-La / Y type molecular sieve and Fe-Co / activated carbon is the same as that of Ni-W / Al2O3
[0024] Preparation of Pt-Ni / SiO2-CeO2: Platinum chloride, nickel nitrate solution, silica sol and CeO2 were placed in a beaker, stirred to dry at room temperature, and then placed in a 100°C oven for 12 hours. The resulting catalyst was reduced in a tubular calcining furnace for 3 hours at a reduction temperature of 350°C. Finally, it was aged for 0.5 hours in a mixture of N2: air at a ratio of 5:1.
[0025] The preparation method of Ru-Ir / TiO2 is the same as that of Pt-Ni / SiO2-CeO2.
[0026] Preparation of Cu-Co-Sn / ZSM-5: Copper nitrate, cobalt nitrate, tin chloride, ZSM and urea were placed in a steel autoclave lined with polytetrafluoroethylene in a beaker and heated at 200°C for 24h. After air cooling to room temperature, the precipitate was collected by extraction filtration, washed with water and anhydrous ethanol, and then vacuum dried at 60°C for 5h. The dried sample was then transferred to a tubular calcining furnace, calcined in air at 600°C for 3h, and then reduced in hydrogen at 400°C for 8h to obtain the catalytic material. Finally, it was aged in a mixed gas of N2:air of 5:1 for 2h.
[0027] The preparation method of Cu-Cr-La / Beta molecular sieve is the same as that of Cu-Co-Sn / ZSM-5.
[0028] Preparation of Sn-Mo / ZrO2: Dissolve zirconium isopropoxide, tin chloride and molybdenum chloride in an ethanol solution, adjust the pH with hydrochloric acid and ammonia to obtain a catalyst precursor. Dry the precursor in an oven, and calcine the dried white powder in air at 800°C for 3h, then reduce it in hydrogen at 650°C for 8h. Finally, age it in a mixture of N2:air at a ratio of 5:1 for 0.5h.
[0029] (2) Reaction process
[0030] Example 1.
[0031] A method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid comprises: washing, drying and crushing waste blended textiles (60% cotton-40% polyester), putting the waste blended textiles (waste paper and waste PET bottles can be added, and the mass ratio is maintained at 6:4) into a mixed solvent of water and tetrahydrofuran (3:2) at a mass ratio of 1:20, then adding 25% Ni-W-Al2O3 based on the mass of the blended textiles, filling with 4MPa air, reacting at 175°C with a stirring rate of 500-1000rpm for 12h, filtering out terephthalic acid, catalyst and unreacted blended textiles while hot after the reaction is completed, and then obtaining terephthalic acid monomer by recrystallization. The composition of the small molecule depolymerization product is detected by gas chromatography and high performance liquid chromatography. The yield of α-hydroxy acid = the number of carbon atoms in the α-hydroxy acid product / the number of carbon atoms in the cellulose in the raw material, and the yield of terephthalic acid = the number of moles of terephthalic acid in the product / the number of moles of structural units in the polyester raw material. In this embodiment, the yield of α-hydroxy acid is 75% (including 69% lactic acid and 6% glycolic acid), the yield of terephthalic acid is 91%, and the purity is 99%.
[0032] Example 2.
[0033] A method for oxidatively depolymerizing waste blended textiles into α-hydroxy acid and terephthalic acid, comprising: washing, drying and crushing waste blended textiles (60% regenerated cellulose fiber-20% polyester-20% acetate fiber), placing the waste blended textiles into a mixed solvent of water and isopropanol (1:1) at a mass ratio of 1:15, then adding 15% Pt-Ni-SiO2-CeO2 based on the mass of the blended textiles, charging with air diluted with 8MPa nitrogen (5:1), reacting at 250°C with a stirring rate of 500-1000rpm for 16 hours. After the reaction is completed, terephthalic acid, catalyst and unreacted blended textiles are filtered out while hot. Then, terephthalic acid monomer is obtained by recrystallization. The composition of small molecule depolymerization products is detected by gas chromatography and high performance liquid chromatography. The yield of α-hydroxy acid = the number of carbon atoms in the α-hydroxy acid product / the number of carbon atoms in the cellulose in the raw material, and the yield of terephthalic acid = the number of moles of terephthalic acid in the product / the number of moles of structural units in the polyester raw material. In this embodiment, the yield of α-hydroxy acid is 80% (including 64% lactic acid and 16% glycolic acid), the yield of terephthalic acid is 93%, and the purity is 97%.
[0034] Example 3.
[0035] A method for oxidatively depolymerizing waste blended textiles into α-hydroxy acid and terephthalic acid, comprising: washing, drying and crushing waste blended textiles (30% regenerated cellulose fiber-50% polyester-20% nylon), placing the waste blended textiles into a mixed solvent of tetrahydrofuran, methanol and ethanol (5:3:1) in a mass ratio of 1:10, then adding 19% Cu-Co-Sn-ZSM-5 based on the mass of the blended textiles, charging a mixed gas of 5.5MPa oxygen and nitrogen (9:1), reacting at 205°C with a stirring rate of 500-1000rpm for 26h. After the reaction is completed, terephthalic acid, catalyst and unreacted blended textiles are filtered out while hot. Then, terephthalic acid monomer is obtained by recrystallization. The composition of small molecule depolymerization products is detected by gas chromatography and high performance liquid chromatography. The yield of α-hydroxy acid = the number of carbon atoms in the α-hydroxy acid product / the number of carbon atoms in the cellulose in the raw material, and the yield of terephthalic acid = the number of moles of terephthalic acid in the product / the number of moles of structural units in the polyester raw material. In this embodiment, the yield of α-hydroxy acid is 78% (including 74% lactic acid and 4% glycolic acid), the yield of terephthalic acid is 91%, and the purity is 99%.
[0036] Example 4.
[0037] A method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, comprising: washing, drying and crushing waste blended textiles (33% cotton-33% polyester-33% vinylon), placing the waste blended textiles into a mixed solvent of water and acetonitrile (10:1) at a mass ratio of 1:8, then adding 33% Nb-La / Y molecular sieves based on the mass of the blended textiles, charging a mixed gas of 3MPa oxygen and air (1:1), reacting at 180°C with a stirring rate of 500-1000rpm for 10 hours. After the reaction is completed, terephthalic acid, catalyst and unreacted blended textiles are filtered out while hot. Then, terephthalic acid monomer is obtained by recrystallization. The composition of small molecule depolymerization products is detected by gas chromatography and high performance liquid chromatography. The yield of α-hydroxy acid = the number of carbon atoms in the α-hydroxy acid product / the number of carbon atoms in the cellulose in the raw material, and the yield of terephthalic acid = the number of moles of terephthalic acid in the product / the number of moles of structural units in the polyester raw material. In this embodiment, the yield of α-hydroxy acid is 81% (including 72% lactic acid and 9% glycolic acid), the yield of terephthalic acid is 95%, and the purity is 96%.
[0038] Example 5.
[0039] A method for oxidatively depolymerizing waste blended textiles into α-hydroxy acid and terephthalic acid comprises: washing, drying and crushing waste blended textiles (80% cotton-10% lyocell-8% polyester-2% polyurethane), placing the waste blended textiles into a mixed solvent of methanol, cyclohexane and dichloromethane (5:3:2) in a mass ratio of 1:15, then adding 30% Fe-Co / activated carbon and Ru-Ir / TiO2 (5:1) based on the mass of the blended textiles, filling with 6MPa air, reacting at 225°C with a stirring rate of 500-1000rpm for 15.5h. After the reaction is completed, terephthalic acid, catalyst and unreacted blended textiles are filtered out while hot. Then terephthalic acid monomer is obtained by recrystallization. The composition of small molecule depolymerization products is detected by gas chromatography and high performance liquid chromatography. The yield of α-hydroxy acid = the number of carbon atoms in the α-hydroxy acid product / the number of carbon atoms in the cellulose in the raw material, and the yield of terephthalic acid = the number of moles of terephthalic acid in the product / the number of moles of structural units in the polyester raw material. In this embodiment, the yield of α-hydroxy acid is 81% (including 70% lactic acid and 11% glycolic acid), the yield of terephthalic acid is 97%, and the purity is 99%.
[0040] Example 6.
[0041] A method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid comprises: washing, drying and crushing waste blended textiles (60% cotton-25% polyester-15% acrylic fiber), putting the waste blended textiles into a mixed solvent of water, acetone and dodecane (2:1:1) in a mass ratio of 1:18, then adding 16% Sn-Mo / ZrO2 and Cu-Cr-La / Beta molecular sieve (1:1) based on the mass of the blended textiles, charging 0.9MPa oxygen, reacting at 180°C with a stirring rate of 500-1000rpm for 40h. After the reaction is completed, terephthalic acid, catalyst and unreacted blended textiles are filtered out while hot. Then terephthalic acid monomer is obtained by recrystallization. The composition of small molecule depolymerization products is detected by gas chromatography and high performance liquid chromatography. The yield of α-hydroxy acid = the number of carbon atoms in the α-hydroxy acid product / the number of carbon atoms in the cellulose in the raw material, and the yield of terephthalic acid = the number of moles of terephthalic acid in the product / the number of moles of structural units in the polyester raw material. In this embodiment, the yield of α-hydroxy acid is 78% (including 72% lactic acid and 6% glycolic acid), the yield of terephthalic acid is 98%, and the purity is 99%.
[0042] The above description is only an application implementation mode of the present invention, but the protection scope of the present invention is not limited to this, and the scope of rights of the present invention cannot be limited thereto. Any equivalent changes made according to the technical solution of the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid, characterized in that: The method specifically comprises the following steps: adding waste blended textiles, a solid acid catalyst and a reaction solution into a catalytic reactor, filling a certain amount of air and / or oxygen, heating to a specified temperature and performing oxidative depolymerization under stirring, and completing the reaction. The product is filtered, concentrated and separated and purified to obtain terephthalic acid and α-hydroxy acid, wherein the α-hydroxy acid includes glycolic acid and lactic acid.
2. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 1, characterized in that: The main components of the blended textile are cotton and / or polyester.
3. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 2, characterized in that: The blended textiles also include one or more mixtures of nylon, acrylic fiber, vinylon, acetate fiber, lyocell, polyester, and polyurethane.
4. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 3, characterized in that: The solid acid catalyst comprises at least one metal and its oxide and at least one carrier.
5. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 4, characterized in that: The metal in the solid acid catalyst is a mixture of one or more of Pt, Ru, Ir, Mo, Cu, Co, Ni, Sn, Fe, W, Cr, Nb, and La.
6. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 4, characterized in that The carrier is a mixture of one or more of Al2O3, TiO2, ZrO2, SiO2, CeO2, ZSM-5 molecular sieve, Beta molecular sieve, Y-type molecular sieve and activated carbon.
7. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 4, characterized in that: The mass ratio of the catalyst to the waste blended textiles is 1:1 to 1:
20.
8. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 4, characterized in that: The mass proportion of the waste blended textiles in the solvent is 0.1 to 100%.
9. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 4, characterized in that: The reaction solution is a mixture of one or more of water, methanol, ethanol, isopropanol, acetonitrile, acetone, tetrahydrofuran, dichloromethane, alkanes and cycloalkanes.
10. The method for oxidative depolymerization of waste blended textiles into α-hydroxy acid and terephthalic acid according to claim 4, characterized in that: The reaction temperature is 180-250° C., and the reaction time is 10-40 hours.
Citation Information
Patent Citations
Waste polyester cotton textile recycling system
CN202754932U
Method for isolation of RNA from paraffin-embedded tissue specimens
EA006827B1
Cited By
Method for preparing isosorbide from cotton textile
CN121405710A
A method for preparing isosorbide from cotton textiles
CN121405710B